2018
DOI: 10.1111/jfs.12603
|View full text |Cite
|
Sign up to set email alerts
|

Nontyphoid Salmonella carriage, serovar profile and antimicrobial resistance phenotypes in slaughter cattle

Abstract: Current nontyphoid Salmonella (NTS) carriage in 200 apparently healthy slaughter cattle by ISO 6579 standard bacteriology (ISO) was 1% (2/200) in carcass and fecal content, and 2% (4/200) in mesenterial lymph nodes. There was no isolation from liver, kidney, spleen, and gallbladder, with an overall prevalence of 4% (8/200). Real‐time PCR was in substantial agreement to ISO in confirming Salmonella‐suspect isolates (Relative Trueness: 93.33%). Predominant serovar was S. Enteritidis (50%) followed by S. Typhimur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
3
0
1
Order By: Relevance
“…During this period, 6 full articles and three published abstracts representing 11 datasets were retrieved using the search engines (6775). The majority of these studies were reported from Africa (67, 68, 7074) except for two studies from Europe (69) and South America (75). Among the total of 5,868 cattle examined, 9.2% (554/6018), which is nearly equal to the pooled prevalence estimate, were reported to be positive for Salmonella species with different serotypes.…”
Section: Discussionmentioning
confidence: 99%
“…During this period, 6 full articles and three published abstracts representing 11 datasets were retrieved using the search engines (6775). The majority of these studies were reported from Africa (67, 68, 7074) except for two studies from Europe (69) and South America (75). Among the total of 5,868 cattle examined, 9.2% (554/6018), which is nearly equal to the pooled prevalence estimate, were reported to be positive for Salmonella species with different serotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Las frecuencias de positividad al patógeno aquí observadas (2.5 a 9.7 %), son inferiores a las reportadas en otros trabajos con carne molida (16-68 %) (4,5) y con linfonodos (50-94 %) (6,19,20) . No obstante, la variabilidad de este fenómeno entre zonas geográficas y épocas del año está bien documentada (20,21) . En general, el estudio confirma la importancia de los bovinos aparentemente sanos como reservorio de diversos serotipos de Salmonella de importancia epidemiológica.…”
Section: Discussionunclassified
“…Salmonella is a public health threat that is a key obstacle to safety in the red meat industry (1,3,10,66). A total of 31 Salmonella serotypes including S. Anatum, S. Heidelberg, S. Newport, S. Saintpaul and S. Typhimurium have been flagged as potential adulterants on meat (61).…”
Section: Introductionmentioning
confidence: 99%